Optimalisasi Kinerja Pegawai melalui Sinergi Budaya, Disiplin, dan Motivasi Kerja Biddokkes Polda Lampung - Hakim, Lukmanul; Jeni Lappy; M. Hasan Ma’ruf (JURNAL ILMIAH EDUNOMIKA, 2025)
This study investigates the influence of organizational culture and work discipline on the performance of employees in the Medicine and Health Sector (Biddokkes) of the Lampung Police, as well as evaluating the role of work motivation as a moderation variable. The background of the problem includes the implementation of 3S (Smile, Greeting, Greeting) which is not yet uniform, low time discipline, and uneven awarding which has the potential to reduce work morale. The quantitative method was used with purposive sampling of 84 respondents; data were collected through the Likert questionnaire and analyzed using multiple linear regression and Moderated Regression Analysis (MRA) with SPSS. The results showed that work discipline had a positive and significant effect on employee performance, while organizational culture did not have a significant influence on performance in this context; Work motivation also did not moderate the relationship between culture/discipline and performance significantly. These findings indicate that interventions that focus on discipline enforcement and improvement of reward mechanisms are more urgent to improve performance than efforts to build an organizational culture that has not been internalized. The findings were compared with a local study by IIB Darmajaya that emphasized the role of leadership, rewards, and training in strengthening organizational culture. Practical implications include consistent enforcement of disciplinary rules, standardization of fair and transparent reward mechanisms, internal training for the internalization of 3S values, and periodic performance monitoring with a measurable dashboard. Recommendations for further research include longitudinal studies and award policy experiments. Follow-up studies are suggested involving multi-unit work for stronger generalizations Keywords: organizational culture; work discipline; work motivation; employee performance.